Magnetic resonance elastography vs. point shear wave ultrasound elastography for the assessment of renal allograft dysfunction. Issue 126 (May 2020) - Kennedy, Paul; Bane, Octavia; Hectors, Stefanie J.; Gordic, Sonja; Berger, Mark; Delaney, Veronica; Salem, Fadi; Lewis, Sara; Menon, Madhav; Taouli, Bachir
Highlights: MRE histogram parameters appear sensitive to renal allograft dysfunction. Mean MRE stiffness was a significant predictor of graft loss and relist. pSWE did not differentiate dysfunctional allografts or correlate with pathology. pSWE had a high proportion of unreliable measurements. Abstract: Purpose: To investigate the utility of magnetic resonance elastography (MRE) vs. ultrasound (US) point shear wave elastography (pSWE) for the assessment of chronic renal allograft dysfunction, prediction of outcome and determine the correlation with Banff pathology scores. Methods: In this IRB approved prospective study, 27 enrolled patients with functional (n = 15) and chronic dysfunctional (n = 12) renal allografts underwent same day 2D MRE and pSWE. Histogram parameters [including mean, median, standard deviation, kurtosis and skewness] of the magnitude of the complex shear modulus (MRE) and median Young's modulus (pSWE) were measured in the cortex (MRE and pSWE) and combined corticomedullary regions (MRE). Histopathology was available for 16 patients (4 functional, 12 dysfunctional). Results: MRE and pSWE stiffness were not significantly different between functional and dysfunctional groups (p range 0.139-0.347). The skewness of MRE corticomedullary stiffness was significantly lower (p = 0.04) in patients with chronic dysfunction and correlated significantly with Banff histopathologic scores (range r=-0.518–0.567, p = 0.035–0.040). MRE cortical and corticomedullary mean stiffness showed strong performance in predicting graft loss/relist (AUC 0.958, p = 0.011 for both). Reliable pSWE measurements were obtained in 13 patients (48 %). pSWE stiffness did not correlate with Banff scores and did not predict outcome. Conclusions: The skewness of MRE corticomedullary stiffness is sensitive to changes in chronic allograft dysfunction, while mean/median MRE renal stiffness and median US stiffness did not differentiate patients with stable function vs those with chronic renal allograft dysfunction. MRE corticomedullary mean stiffness appears to be a predictor of graft loss/relist. pSWE was not found to be a useful method for assessing renal allografts.